Eksplorasi Rasa Baru Melalui Inovasi Isian Choux Kolak Pisang untuk Meningkatkan Daya Tarik Menu - Diah Banyuni; Fuji Safira (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
Choux craquelin is a variation of choux pastry characterized by a layer of dough on top, commonly referred to as craquelin, which becomes crunchy after baking. The primary ingredient used is wheat flour. The filling for choux typically consists of a cooled custard or cream, usually flavored with vanilla or fruit slices. In this instance, the author attempts to create a new flavor innovation for the choux au craquelin filling using kolak pisang. Kolak pisang is a sweet dish made with coconut milk and brown sugar, accompanied by the fragrant aroma of bananas, and is commonly enjoyed during certain occasions, such as Ramadan. The aim of this research is to determine the standard recipe, the level of preference for the product, and a business analysis. This study employs a research and development approach, and data collection was conducted through organoleptic testing with five expert panelists. The findings indicate that the appropriate standard recipe consists of the following: choux: 200g eggs, 120g water, 120g UHT milk, 100g margarine, 2g salt, and 150g wheat flour; craquelin: 100g butter, 100g wheat flour, and 90g granulated sugar; kolak pisang cream: 250g whipped cream, 7 pieces of jackfruit bananas, 200g palm sugar, 3 pandan leaves, 1g salt, 100g instant coconut milk, and 200g palm sugar. The business analysis revealed a food cost of Rp. 2,870 per piece, with a selling price of Rp. 8,000. The break-even point is reached by selling 442 pieces. To achieve a target profit of Rp. 3,000,000 per month, the author must sell 1,451 pieces per month. This research hopes to contribute to innovative developments in kolak pisang-based products.